(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Aim and objective: To evaluate the usefulness of otoacoustic emissions and brainstem evoked response audiometry for assessment of hearing loss in newborn. Materials and Method: Total of 370 healthy newborns were subjected to ENT examination, otoacoustic emissions (OAE) within 3 days to 30 days of birth. All newborn with normal hearing at OAE were not studied further, and for refer cases OAE testing was carried out again at 3rd month of age. The infants who failed the second OAE were subjected to brainstem evoked response audiometry (BERA). All newborn with abnormal BERA were subjected to repeat BERA at 6th month of age. Results: All 370 healthy enrolled babies underwent OAE testing. Of which 200 (54.05%) passed the test and 170 (45.95 %) were referred. All 170 referred babies underwent repeat OAE at age of 3 months. Of which 50 passed the test and 120 were referred again. All these 120 referred cases were subjected to further testing using BERA between the ages 3-4 months. 2 were found to be having profound hearing loss during BERA testing at 3-4 months as well as at 6 months. Conclusion: Profound hearing loss was found in 2 out of 370 enrolled normal newborn. This also means that if only ‘at risk’ babies were screened there is likely chance of missing impaired hearing in newborn without any risk factor. Hence, during hearing assessment it is mandatory to include all newborns irrespective of their status normal or ‘at risk’.